A Model for Public Libraries' Support in the Development of Small-Scale Business Enterprises in Meru County, Kenya. Issue 1 (2nd January 2018) - Gichohi, Paul Maku; Onyancha, Omwoyo Bosire; Dulle, Frankwell W.
ABSTRACT: This study aims at developing a suitable model for support by public libraries in the development of small-scale business enterprises (SBEs) in Meru County, Kenya. A mixed-methods research approach and survey research design were applied. We collected data from small-scale business traders, staff members from the three public libraries, and two staff members in charge of the Enterprise Development Department in Meru County by means of questionnaires and interviews, and applied document analysis on written sources held by these entities. We developed a model that can be adopted and is highly recommended to public libraries in supporting small enterprises in Kenya.